1996
DOI: 10.1136/thx.51.10.1010
|View full text |Cite
|
Sign up to set email alerts
|

Community acquired pneumonia: aetiology and usefulness of severity criteria on admission.

Abstract: Background-Community acquired pneumonia remains an important cause ofhospital admission and carries an appreciable mortality. Criteria for the assessment of severity during admission have been developed by the British Thoracic Society (BTS). A study was performed to determine the sensitivity and specificity of a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
267
3
21

Year Published

1999
1999
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(304 citation statements)
references
References 18 publications
(3 reference statements)
9
267
3
21
Order By: Relevance
“…Several studies could confirm excellent operative characteristics of the original [24,25] or a slightly modified rule [26]. The sensitivities ranged from 70±90%, and the specificities from 76±84% (table 6).…”
Section: Prognostic Rules For the Individual Hospitalized Patientmentioning
confidence: 93%
“…Several studies could confirm excellent operative characteristics of the original [24,25] or a slightly modified rule [26]. The sensitivities ranged from 70±90%, and the specificities from 76±84% (table 6).…”
Section: Prognostic Rules For the Individual Hospitalized Patientmentioning
confidence: 93%
“…4 8 This prediction tool has been independently validated and widely endorsed. 2 3 9-11 N The CURB index 6 was derived from the original BTS study 12 and uses four core clinical features: confusion of new onset (or worsening of existing state for those with background cognitive impairment), serum urea .7 mmol/ l, respiratory rate >30/min, and blood pressure (systolic blood pressure ,90 mm Hg or diastolic blood pressure (60 mm Hg). The presence of two or more of these four criteria led to a ''severe'' classification.…”
Section: Methodsmentioning
confidence: 99%
“…Three validation studies of the BTS rules, in different settings, confirmed the potential of these rules in identifying patients at risk of death caused by pneumonia [6±8]. However, these rules were derived in general populations, and the BTS derivation study [4] as well as some of the validation studies of the BTS rules [7,8] excluded part of the elderly population. Therefore, there remained concerns about the validity of these rules in community-acquired pneumonia in the elderly [9].…”
mentioning
confidence: 99%